2012
DOI: 10.1111/j.1754-9485.2012.02348.x
|View full text |Cite
|
Sign up to set email alerts
|

Common patterns in 558 diagnostic radiology errors

Abstract: Introduction: As a Quality Improvement initiative our department has held regular discrepancy meetings since 2003. We performed a retrospective analysis of the cases presented and identified the most common pattern of error. Methods: A total of 558 cases were referred for discussion over 92 months, and errors were classified as perceptual or interpretative. The most common patterns of error for each imaging modality were analysed, and the misses were scored by consensus as subtle or non-subtle. Results: Of 558… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
87
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(96 citation statements)
references
References 20 publications
6
87
2
1
Order By: Relevance
“…Occasionally, as in cases of neck or abdominal computed tomography (CT) scans, additional specific sites (i.e., a part of the chest) may inevitably be included and also need to be interpreted correctly. Incidental but potentially important findings outside the area of interest may be present but missed in any radiologic studies (2)(3)(4)(5)(6). We have occasionally found chest lesions that were not reported on neck CT interpretations when follow-up neck or chest CT studies were performed and compared with a previous neck CT study.…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…Occasionally, as in cases of neck or abdominal computed tomography (CT) scans, additional specific sites (i.e., a part of the chest) may inevitably be included and also need to be interpreted correctly. Incidental but potentially important findings outside the area of interest may be present but missed in any radiologic studies (2)(3)(4)(5)(6). We have occasionally found chest lesions that were not reported on neck CT interpretations when follow-up neck or chest CT studies were performed and compared with a previous neck CT study.…”
Section: Introductionmentioning
confidence: 81%
“…Other studies have reported that if the first radiologist misses a finding, the next radiologist will likely miss it as well (8,12). There are only a few studies which investigated common errors in the interpretation of head and neck CT scans, none of which focused on missed chest lesions (2,13,14). One study showed that vascular lesions, such as aneurysm, were most commonly missed on head and neck CT angiography, and neck mass, sellar mass, and nasogastric tube malposition were also missed as well (13).…”
Section: Discussionmentioning
confidence: 99%
“…P erceptual errors account for a substantial part of misdiagnoses in radiology (1) and can be related to the search behavior of the observer (2). For educational purposes, it is important to identify which visual search patterns are most effective and to investigate if teaching search strategies improves perception.…”
Section: Introductionmentioning
confidence: 99%
“…Perceptual errors account for 48%-80% of all diagnostic radiology errors reported in the literature [1,2]. While the underlying reasons for perceptual errors are not well understood, there is considerable evidence that argues strongly against the concept that visual errors are the result of carelessness, sloppiness or negligence on the part of radiologists [3].…”
Section: Introductionmentioning
confidence: 99%